Rok 1338 w ustrojowo-prawnych dziejach Śląska - Ptak, Marian J. (Wydawnictwo Uniwersytetu Wrocławskiego, 2020)
The article is an attempt to examine the political and legal events in Silesia in 1338, usually left out of analyses because of their authors’ concentration on the previous year. The present author tackles the problem of vassal dukes of Głogów, their fi ght for the Duchy of Głogów, political activity of free dukes in the Duchy of Świdnica and Jawor, union of the Duchies of Opava and Racibórz as well as royal territories in Silesia and their system of governance.
Keywords: Śląsk; księstwa śląskie; rok 1338; system polityczny; prawo